Efficient records management via SSMSS: the concept, development and future planning / Mahfudzah Othman, Mohd Norafizal A. Aziz and Zainab Othman - Othman, Mahfudzah; A. Aziz, Mohd Norafizal; Othman, Zainab (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
The School’s Student Management System (SSMSS) is a web-based application system built to manage students’ records in schools. The study has started since 2003 and was motivated due to today’s demand of moving towards the paperless environment. This web-based system has been developed using high end technologies such as MySQL database, PHP and Apache as the web server and has gone through many series of modification to suit the users’ requirements. The main objective of this study is to introduce a more efficient records management in schools around Jengka district. This is due to the fact that in rural areas, the records management in schools is quite poor and seems to be left behind in terms of information technology and communication (ICT) development. SSMSS offers a lot of benefits such as it can be accessed via the Web simultaneously thus supporting multi-users from dispersed locations. This web-based system is hoped to not only enhance the records management processes, but it will also help to improve the development of ICT in rural community. This paper will discuss more intensively about the concept and development of SSMSS, the benefits that it could offer, achievements over the years and the strategic planning for future development.